Anti-Inflammatory And Analgesic Activities Of Ligustrum Robustum In Experimental Animal Models - ANANYA CHAKRABORTY; USHAM DHARMARAJA MEETEI; SUBHALAKSHMI AKHAM (International Journal of Pharma and Bio Sciences, 2012)
Ligustrum robustum is an indigenous medicinal shrub that belongs to the family, Oleaceae. It is a major component of Chinese tea, Ku-Ding-Cha, which is used to prevent common cold, rhinitis, itching eyes, and headache. The present study was undertaken to evaluate the anti-inflammatory and analgesic activities of the aqueous extract of Ligustrum robustum (ALR) in experimental animal models. ALR was evaluated for anti-inflammatory action by carrageenan induced rat paw edema. The analgesic activity was assessed by tail flick response in albino rats and writhing response in albino mice. ALR in dose of 200 mg/kg showed 39% inhibition of paw edema. In the tail flick model, ALR increased the pain threshold significantly after 30 min and 1h of administration. The percentage protection of writhing with ALR was 46.9% which indicates that ALR has significant anti-inflammatory and analgesic properties.